PiggyBac-Generated CAR19-T Cells Plus Lenalidomide Cause Durable Complete Remission of Triple-Hit Refractory/Relapsed DLBCL: A Case Report - Li, Chenggong; Sun, Yan; Wang, Jing; Tang, Lu; Jiang, Huiwen; Guo, Tao; Liu, Lin; Wu, Yaohui; Ai, Lisha; Xia, Linghui; Wu, Jianjun; Lin, Zhicai; et al. (Frontiers in Immunology, 2021)
MYC/BCL2/BCL6 triple-hit lymphoma(THL) is an uncommon subset of high-grade B-cell lymphoma with aggressive clinical behavior and poor prognosis. TP53 mutation is an independently poor progonistic indicator in patients with THL, hence novel therapeutic strategies are needed for these patients. CD19-directed chimeric antigen receptor(CAR19)-T cell therapy has shown promising efficacy for relapsed/refractory diffuse large B cell lymphoma(RR DLBCL), but the majority of CAR19-T cell products to date have been manufactured using viral vectors. PiggyBac transposon system, with an inclination to memory T cells, offers a more convenient and economical alternative for transgene delivery. We herein report the first case of triple-hit RR DLBCL with TP53 mutation who was treated with piggyBac-generated CAR19-T cells and accompanied by grade 2 cytokine release syndrome. The patient obtained a complete remission(CR) in the 2nd month post-infusion and demanded maintenance therapy. Whether maintenance therapy is favorable and how to administrate it after CAR-T cell infusion remain controversial. Preclinical studies demonstrated that lenalidomide could enhance antitumor activity of CAR19-T cells. Therefore, we pioneered oral lenalidomide after CAR19-T therapy in the patient from the 4th month, and he discontinued after one cycle due to side effects. The patient has still kept sustained CR for over 24 months. Our case have firstly demonstrated the feasibility, preliminary safety and efficacy of piggyBac-produced CAR19-T cell therapy in triple-hit lymphoma. The innovative combination with lenalidomide warrants further investigation. Our findings shed new light on the possible solutions to improve short-term relapse after CAR19-T cell therapy in RR DLBCL. ChiCTR, number ChiCTR1800018111.